Cervical Cancer and Ethical issues in HPV Vaccination - Haseen, Fariha; Sony, Sadia Akther (Bangladesh Journal of Bioethics, 2017)
Human Papilloma Virus (HPV) infection causes death of 270,000 people die from every year. Sexually transmitted HPV was found one of the major causes of cervical cancer. World Health Organization (WHO). Cervical cancer (CC) is one of the top five cancers that affect women around the world. In June 2006, the Food and Drug Administration (FDA) approved a new vaccine for women, Gardasil, produced by the pharmaceutical company Merck that protects against infection by certain strains of HPV, including the two strains that cause most cases of cervical cancer. Vaccinations are counted as one of public health’s important development but there is an ethical dilemma between balancing personal autonomy and protection of the entire at risk population. The vaccine caused very few side effects like local reactions whereas signs or symptoms of greater importance were very. Moreover it was considered that the vaccine is has an efficacy of practically 100% in prevention of precancerous lesion caused by the viral genotypes included in the vaccine. Bioethicists were not convinced about compulsory vaccination laws as the values of patient autonomy and informed consent to be preeminent to them. Not surprisingly, some have expressed wariness about or opposition to mandating HPV vaccination. A critical question is whether achieving a higher level of coverage justifies the infringement on parental autonomy that compulsory vaccination inevitably entails. Recommendation of the universal vaccination of girls and young women may evolve ethical challenges which might make it difficult for smooth implementation of the vaccination campaigns. Review of the ethical issues in HPV vaccination will constitute the main part of our paper.